Governance questions for the international community - Betts, A (Refugee Studies Centre, University of Oxford, 2015)
The Nansen Initiative has highlighted significant questions about how the international community should collectively think about displacement and mobility issues relating to natural disasters and climate change, and how to improve the governance thereof.